EFFECT OF STORAGE DURATION AND LOW TEMPERATURES ON THE DEVELOPMENTAL STAGES OF CHRYSOPERLA CARNEA (STEPHENS) (NEUROPTERA: CHRYSOPIDAE) - S. Nadeem; M. Hamed; M. Ishfaq; M. K. Nadeem; M. Hasnain; N. A. Saeed (Journal of Animal and Plant Sciences, 2014)
Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) known as common green lacewing, its adult feeds only on plant nectars and larva is the voracious feeder of aphids and hence used in biological control of insect pests. In present study, the effective storage temperatures at optimum durations for the developmental stages of C. carnea under laboratory conditions was carried out. The consequence of storage duration and low temperatures on the different developmental stages of C. carnea at egg, larval, pre-pupal and pupal stages revealed that the storage of eggs at temperatures of 6, 12, 14 and 16oC gave short term storage up to 15-20 days with minimum detrimental effects to the developing embryo. Whereas, 8 and 10oC conditions of storage suited for both short and long term storage for 40 days. It is inferred from the results that whenever, needed to conserve strains of C. carnea in laboratories for experimentation or field releases, the storage at low temperatures of 8oC proved effective for both short and long term durations.
Keywords: Storage temperature; duration; Chrysoperla carnea